2007
DOI: 10.1210/en.2007-0863
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interferon (IFN)-Stimulated Genes in Extrauterine Tissues during Early Pregnancy in Sheep Is the Consequence of Endocrine IFN-τ Release from the Uterine Vein

Abstract: The ruminant conceptus synthesizes and secretes interferon (IFN)-tau, which presumably acts via an intrauterine paracrine mechanism to signal maternal recognition of pregnancy. The aims of this study were to determine whether IFN-stimulated genes (ISG) such as ISG15 and OAS-1 are differentially expressed in blood cells circulating in the uterus of ewes; whether extrauterine components of the reproductive tract such as the corpus luteum (CL) also express mRNA for these ISG, and whether antiviral activity is gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 44 publications
6
154
1
8
Order By: Relevance
“…Oliveria et al [34] demonstrated greater antiviral activity in uterine vein blood from Day15 pregnant sheep. Additionally, Bott et al [35] showed that preadsorption of blood by IFNT antibody reduced this antiviral activity, suggesting the release of IFNT into the uterine vein during the MRP.…”
Section: Discussionmentioning
confidence: 97%
“…Oliveria et al [34] demonstrated greater antiviral activity in uterine vein blood from Day15 pregnant sheep. Additionally, Bott et al [35] showed that preadsorption of blood by IFNT antibody reduced this antiviral activity, suggesting the release of IFNT into the uterine vein during the MRP.…”
Section: Discussionmentioning
confidence: 97%
“…Dados recentes reportam a expressão de ISGs no CL e em outros tecidos extrauterinos durante o início da prenhez em ovelhas, sugerindo uma ação endócrina do IFNT (OLIVEIRA et al, 2008). A ISG15 (gene estimulado por inteferon 15) é uma proteína que possui função semelhante a uma ubiquitina (AUSTIN et al, 1996) e é expressa no útero durante o início da gestação em resposta ao IFNT.…”
Section: O Reconhecimento Materno Da Gestação é O Período Em Que O Counclassified
“…A ISG15 (gene estimulado por inteferon 15) é uma proteína que possui função semelhante a uma ubiquitina (AUSTIN et al, 1996) e é expressa no útero durante o início da gestação em resposta ao IFNT. Contudo, por meio de imunohistoquímica, sua presença foi também detectada em células luteais grandes do CL de ovelhas no dia 15 da gestação (OLIVEIRA et al, 2008). A ação endócrina do IFNT foi corroborada pela infusão de IFNT recombinante ovino (roIFNT), por sete dias, na veia uterina de ovelhas (BOTT et al, 2010).…”
Section: O Reconhecimento Materno Da Gestação é O Período Em Que O Counclassified
See 1 more Smart Citation
“…Mann and Lamming (1999) effects on the endometrium, but also effects on cells in other tissues (HICKS et al, 2003;GIFFORD, 2010). Interferon-τ exits the uterus and reaches the maternal circulation (Oliveira et al, 2008), which induces expression of genes in blood leukocytes (GIFFORD et al, 2008;OLIVEIRA et al, 2008). In fact, mRNA abundance for ISG in leukocytes parallels the VAN CLEEFF et al, 1996).…”
Section: Discussionmentioning
confidence: 99%